The Nexus between individual interest and school engagement in bolstering Physical Culture for a habitual healthy régime: a case of a state university - Clarenz Bautista; Don Al De Dios; Joseph Lobo (Physical Education of Students, 2023)
Background and Study Aim. A worldwide consensus exists that students' levels of interest strongly predict and trigger their engagement in various activities, particularly those that promote physical culture. Academic works in the field of Physical Education have demonstrated that students can be extremely engaged when they are exposed to situations that pique their interest. However, the relationship and influence of students’ individual interests on their engagement in school have not yet been documented further. Hence, conducting an investigation should be performed.